2021
DOI: 10.1186/s12936-021-03817-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-tocopheryloxy acetic acid, a vitamin E derivative mitocan, on the experimental infection of mice with Plasmodium yoelii

Abstract: Background Malaria parasites are known to be vulnerable to oxidative stress. In this study, the effects of the administration of α-tocopheryloxy acetic acid (α-TEA), which is a vitamin E analogue mitocan, on Plasmodium yoelii infection in mice were examined. Methods Alpha-TEA was mixed with diet and fed to C57BL/6J mice before and/or after infection. For parasite infection, 4 × 104 red blood cells infected with P. yoelii (strain 17XL) were inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…α-TS is unstable under physiological conditions because of cellular esterases' activity. To overcome this problem, the succinic moiety was substituted by an acetic acid part linked to the phenolic oxygen by ether linkage to give α-tocopheryloxyacetic acid (α-TEA) with a stable, non-hydrolysable entity [21][22][23][24][25][26]. This α-tocopherol derivative can be administered orally with high antitumor efficacy [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…α-TS is unstable under physiological conditions because of cellular esterases' activity. To overcome this problem, the succinic moiety was substituted by an acetic acid part linked to the phenolic oxygen by ether linkage to give α-tocopheryloxyacetic acid (α-TEA) with a stable, non-hydrolysable entity [21][22][23][24][25][26]. This α-tocopherol derivative can be administered orally with high antitumor efficacy [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, the succinic moiety was substituted by an acetic acid part linked to the phenolic oxygen by ether linkage to give α-tocopheryloxyacetic acid (α-TEA) with a stable, non-hydrolysable entity [21][22][23][24][25][26]. This α-tocopherol derivative can be administered orally with high antitumor efficacy [26,27]. Studies in the past decade have shown that α-TEA is a potent inducer of apoptosis in various types of cancer epithelial cells [28] in tests both in vitro and in vivo [29].…”
Section: Introductionmentioning
confidence: 99%